1998
DOI: 10.1037/0735-7028.29.1.86
|View full text |Cite
|
Sign up to set email alerts
|

National survey of psychology internship directors regarding education for prevention of psychologist–patient sexual exploitation.

Abstract: All directors of psychology internships accredited by the American Psychological Association (N = 410) were surveyed about the status of internship education related to prevention of psychologistpatient sexual exploitation. Virtually all responding directors (99% of 230) reported that thenprogram provides at least 1 session on this topic, and the same number indicated that such education should be part of the mandatory internship curriculum. Ninety-four percent of responding programs had instituted the reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A variety of other topics were investigated, including education for the prevention of psychologist-patient sexual exploitation (Samuel & Gorton, 1998). Internship directors reported that their programs provided at least one session devoted to this topic and agreed that such education should be mandatory.…”
Section: What Interns Are and Should Be Taughtmentioning
confidence: 99%
“…A variety of other topics were investigated, including education for the prevention of psychologist-patient sexual exploitation (Samuel & Gorton, 1998). Internship directors reported that their programs provided at least one session devoted to this topic and agreed that such education should be mandatory.…”
Section: What Interns Are and Should Be Taughtmentioning
confidence: 99%
“…Until we live in a world in which there are no hunters, vulnerable children and adults will be sitting prey for perpetrators seeking an easy mark. Samuel and Gorton (1998) argued for prevention of sexual exploitation of clients via substantial education in graduate school and in continuing education in psychology. This is good advice for all professions.…”
Section: Implications For Practicementioning
confidence: 99%
“…We agree with other authors (Crewe, 1994;Fly et al, 1997;Kramen-Kahn & Hansen, 1998;Lamb et al, 1987Lamb et al, , 1991Stadler et al, 1988) who have called for the intro-duction into the curriculum of psychology training programs a module (perhaps in ethics courses) on the conceptual and empirical knowledge about the evaluation, identification, remediation, and prevention of impairment, and the professional issues associated with these topics. Introducing topics such as the effects of psychological distress on professional functioning (Ackerley et al, 1988;Sherman & Thelen, 1998) and the responsibility to monitor levels of stress, develop strategies for coping and self-care, and maintain professional functioning would alert students to the professional demands and the need to develop preventive strategies for avoiding impaired performance (Coster & Schwebel, 1997;Hebert, 1992;Kramen-Kahn & Hansen, 1998;Samuel & Gorton, 1998;Schwebel & Coster, 1998;Skorupa & Agresti, 1993). Introducing topics such as the effects of psychological distress on professional functioning (Ackerley et al, 1988;Sherman & Thelen, 1998) and the responsibility to monitor levels of stress, develop strategies for coping and self-care, and maintain professional functioning would alert students to the professional demands and the need to develop preventive strategies for avoiding impaired performance (Coster & Schwebel, 1997;Hebert, 1992;Kramen-Kahn & Hansen, 1998;Samuel & Gorton, 1998;Schwebel & Coster, 1998;Skorupa & Agresti, 1993).…”
Section: Recommendations For Education and Trainingmentioning
confidence: 99%
“…Current students need to have full and accurate information about historical and current efforts to assist distressed psychologists and the anecdotal and empirical evidence about the difficulties both psychologists and trainees have in responding to impaired colleagues (Bernard & Jara, 1986;Bernard, Murphy, & Little, 1987;Chauvin & Remley, 1996;Good et al, 1995;Kaslow & Rice, 1985;Kilburg et al, 1986;Smith, McGuire, Abbott, & Blau, 1991;Steward, Know, & Satterfield, 1988;Thoreson et al, 1986;Wilkins, McGuire, Abbott, & Blau, 1990;Wood, Klein, Cross, Lammers, & Elliott, 1985;Zemlick, 1980). Introducing topics such as the effects of psychological distress on professional functioning (Ackerley et al, 1988;Sherman & Thelen, 1998) and the responsibility to monitor levels of stress, develop strategies for coping and self-care, and maintain professional functioning would alert students to the professional demands and the need to develop preventive strategies for avoiding impaired performance (Coster & Schwebel, 1997;Hebert, 1992;Kramen-Kahn & Hansen, 1998;Samuel & Gorton, 1998;Schwebel & Coster, 1998;Skorupa & Agresti, 1993). Similarly, instruction on the legal requirements of the ADA will help students understand prejudicial attitudes and biases about disability that result in discrimination and denial of access or opportunity as well as the relationship among functional limitations, appropriate accommodations, and essential functions of the profession (Crewe, 1994).…”
Section: Recommendations For Education and Trainingmentioning
confidence: 99%